Association of the Total White Blood Cell, Neutrophils, and Monocytes Count With the Presence, Severity, and Types of Carotid Atherosclerotic Plaque - Liu, Yanhua; Zhu, Yongjian; Jia, Wenrui; Sun, Dan; Zhao, Li; Zhang, Chen; Wang, Cuicui; Lyu, Quanjun; Chen, Yuming; Chen, Gaiyun; Bo, Yacong; Xing, Yurong (Frontiers in Medicine, 2020)
Background: Previous studies have indicated that white blood cells (WBCs) might contribute to the development of atherosclerosis. However, the associations of WBCs and WBC subgroups with carotid atherosclerotic plaque (CAP) have not been compared. Methods: A cross-sectional study including 3,569 healthy Chinese adults was conducted between January 2016 and December 2018 in Zhengzhou, China, to explore the associations of WBC and WBC subtypes with the presence, severity, and types of CAPs. Fasting peripheral venous blood was collected for measurement of the total WBC and WBC subtype counts. The size, composition, and types of CAPs in the common carotid artery, the internal carotid artery, and the external carotid artery were measured bilaterally using B-mode ultrasound. Results: The total WBC, neutrophil, and monocyte counts showed significant associations with the presence of CAPs in men, but not in women, with the adjusted odds ratios (95% CI) in the highest (compared to the lowest) quartile 1.99 (1.33–2.97), 1.65 (1.10–2.47), and 2.17 (1.41–3.18) (Ptrend = 0.004, Ptrend = 0.004, and Ptrend < 0.001), respectively. The three leukocyte counts were also significantly associated with the severity of CAPs, as judged by the count of CAPs, maximal internal carotid plaque thickness, and the plaque score (all P < 0.01, Ptrend < 0.05). Compared with individuals without CAPs, those with echolucent plaques had significantly increased total WBC and neutrophil counts, whereas those with polytype plaques had a significantly increased monocyte count. Conclusion: WBC, neutrophil, and monocyte counts were significantly associated with the presence, severity, and types of CAPs in a healthy Chinese population.